أثر النافذة السكانية في التنمية الاقتصادية والاجتماعية في سورية - الناصر منذر (Latakia University Journal - Economic and Legal Sciences Series, 2019)
بالرغم من اختلاف مشكلات البلدان النامية الاقتصادية والاجتماعية والتنموية, إلا أنها تشترك في السبب الأساس لهذه المشكلات ألا وهو النمو السكاني المرتفع, الذي يمكن أن يشكل بوضعه الحالي عائقا كبيراً أمام كل إمكانية للتحديث والتطوير في هذه البلدان. يعالج البحث الفرصة التنموية الاستثنائية المتمثلة ببوادر انفتاح النافذة السكانية من خلال عرض متزايد من القوة البشرية وتقلص نسبي في معدلات الإعالة والخصوبة, إلا أنها تواجه بمشكلة ضعف الإدخار والاستثمار ومدى مقدرتهما على رفع معدل النمو الاقتصادي وخلق فرص عمل تمتص البطالة. مما يزيد من احتمالات عدم الاستفادة من الهبة السكانية وتسخيرها في خدمة التنمية. من هنا، فإن دراستنا ستتضمن أثر النافذة السكانية في بعض متغيرات التنمية الاقتصادية والاجتماعية كالصحة – التعليم – الاستثمار- تنمية الموارد البشرية... وسنوضح من خلال الدراسة أهم معوقات التنمية, كالنمو السكاني المرتفع ووجود تراكيب عمرية غير ملائمة للنشاط الاقتصادي, وتواضع الأداء الصحي والتعليمي .. الخ. In spite of the different socioeconomic problems of developing countries, they collaborate of the fundamental cause which is the high population growth that is considered a main retardant of all possibilities of modernization and development of these countries. This research treats the relationship between demographic window and many of socioeconomic growth variables, especially that the population is considered the basis engine for every development, and it is considered the true fortune of society, that they are liable of the responsibility of modernization and development. According to what we have said, our study will include the impact of population growth on the following socioeconomic and growth variables: health, education, investment … We will illustrate through the study the most important growth retardants as high population growth, available of age structures, which is not appropriate for economic activity, and modesty of healthy and educational performance …. Etc